Physical mechanisms of meteorological drought development, intensification and termination: an Australian review - Chiara M. Holgate; Georgina M. Falster; Zoe E. Gillett; Pallavi Goswami; Matthew O. Grant; Sanaa Hobeichi; David Hoffmann; Xiaoxuan Jiang; Chenhui Jin; Xiancheng Lu; Mengyuan Mu; Jon Cranko Page; et al. (Communications Earth & Environment)
Abstract We synthesise advances in the understanding of the physical processes that play a role in developing, intensifying, and terminating meteorological droughts. We focus on Australia, where new understanding of drought drivers across different climate regimes provides insights into drought processes elsewhere in the world. Drawing on observational, climate model and machine learning-based research, we conclude that meteorological drought develops and intensifies largely through an absence of synoptic processes responsible for strong moisture transport and heavy precipitation. The subsequent presence of these synoptic processes is key to drought termination. Large-scale modes of climate variability modulate drought through teleconnections, which alter drought-determining synoptic behaviour. On local scales, land surface processes play an important role in intensifying dry conditions and propagating meteorological drought through the hydrological cycle. In the future, Australia may experience longer and more intense droughts than have been observed in the instrumental record, although confidence in drought projections remains low. We propose a research agenda to address key knowledge gaps to improve the understanding, simulation and projection of drought in Australia and around the world.